2017
DOI: 10.1007/s00330-017-5072-9
|View full text |Cite
|
Sign up to set email alerts
|

Hip shape is symmetric, non-dependent on limb dominance and gender-specific: implications for femoroacetabular impingement. A 3D CT analysis in asymptomatic subjects

Abstract: • Hip shape is symmetrical regardless of limb dominance. • Pincer/cam morphology is frequent in asymptomatic subjects (20 and 71%, respectively). • LCEA and acetabular version increases with age (5-7° between opposite age groups). • Femoral morphology is stable after physeal closure (in the absence of pathology). • Alpha and omega angle thresholds should be set according to sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(58 citation statements)
references
References 78 publications
3
55
0
Order By: Relevance
“…Reference intervals (defined by a specific clinical outcome): Whereas the 97.5 percentile (upper limit) for, for example, the α values in the general population lies between 70 and 77 degrees, 51,52 the upper reference limits for α as defined by a specific clinical outcome (hip pain) would correspond to 57 to 60 degrees (which in turn corresponds approximately to the 50-75th percentile of the "epidemiological RefInt"). These values were determined having a specific clinical outcome in mind because they were associated with hip pain in specific studies.…”
Section: Which Population To Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Reference intervals (defined by a specific clinical outcome): Whereas the 97.5 percentile (upper limit) for, for example, the α values in the general population lies between 70 and 77 degrees, 51,52 the upper reference limits for α as defined by a specific clinical outcome (hip pain) would correspond to 57 to 60 degrees (which in turn corresponds approximately to the 50-75th percentile of the "epidemiological RefInt"). These values were determined having a specific clinical outcome in mind because they were associated with hip pain in specific studies.…”
Section: Which Population To Studymentioning
confidence: 99%
“…9a), resulting in the L-CEA. 51,57,58 Surprisingly, the W-CEA is often connected with Ogata et al 59 and the L-CEA with Wiberg. 56 However, Ogata et al 59 suggested the same measurement as described earlier by Wiberg.…”
Section: Acetabular Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hip joint imaging has been a personal enthusiasm of ours in both research and clinical practice. 1,2 It is our pleasure to present an issue on these topics with high-quality contributions from MSK radiologists and orthopaedic surgeons. These articles offer both an overview of current clinical perspectives and state-of-the-art imaging and also in-depth information of paramount significance for daily activities.…”
mentioning
confidence: 99%